Osteogenesis and Ototoxicity of a Novel Preparation of Autogenous Bone Cement: Implications for Mastoid Obliteration. (25th September 2014) - Zou, Wenting; Chen, Xihui
Abstract : Objective: To study the osteogenesis and ototoxicity of autogenous bone cement. Study Design: A randomized, prospective, controlled animal study. Setting: University laboratory. Subjects and Methods: We created a critical defect on the bulla wall of guinea pigs. Fifty‐three guinea pigs were divided into 3 groups. The defects were filled with autogenous bone cement (ABC) or autogenous bone dust (ABD) on the left side while the contralateral sides were kept intact as the blank control (BC) group or a defect was induced without obliteration as the operation control (OC) group (groups 1 and 2, n = 25 each). The animals were sacrificed at 2, 4, 8, and 12 weeks postoperatively. Group 3 (n = 3) was the ototoxicity positive control (OPC) group. The critical defects were evaluated for bone repair by histologic observation and computed tomography (CT), and the ototoxicity of the material was assessed by measuring shifts in the hearing threshold and changes in cochlear morphology. Antibiotic susceptibility testing of the material was also performed. Results: Histologic observation and CT scans revealed complete bone repair in the ABC group at 12 weeks postoperatively, but progress was slower in the ABD group. The hearing threshold and cochlear morphology did not differ significantly between the preoperative and 12‐week postoperative measurement. Autogenous bone dust inhibited some of the bacterial species commonly associated with chronic suppurative otitis media. Conclusions: Animals treated with ABC exhibited osteogenesis, with no ototoxicity and bacteriostasis compared with the use of ABD.